Journal of legal, ethical and regulatory issues: an archive of 23 years in legal, ethical and regulatory issues research - Ali Mohamed, Ashgar Ali; H. Malkawi, Bashar (2020)
The Journal of Legal, Ethical and Regulatory Issues (JLERI) is an open access academic and professional journal affiliated to the Allied Business Academies.